Acute salivary cortisol response in children with ADHD during psychosocial intervention with and without therapy dogs - Schuck, Sabrina E. B.; Zeiler, Cassie N.; Stehli, Annamarie; Steinhoff, Lydia A.; Stokes, Rachel Y.; Jeffrey, Sara E.; Granger, Douglas Alan (Frontiers in Psychiatry, 2024)
This brief report describes effects of Animal Assisted Intervention (AAI) on acute HPA axis activity in children with Attention Deficit/Hyperactivity Disorder (ADHD) participating in a randomized clinical trial comparing AAI to psychosocial treatment as usual (TAU). Thirty-nine participants (n = 39), aged 7-9 years (79% male) provided saliva at 3 points during 90-minute sessions; (i) upon arrival, (ii) +20 minutes, and (iii) 15 minutes prior to departure, on 3 occasions across an 8-week intervention (weeks 1, 4, and 8). Cortisol slopes calculated within session were compared across the intervention to determine within subject and between group effect sizes. Spearman's correlations between baseline individual symptoms and in-session cortisol responses were evaluated.No significant between group differences were observed at week-1. By week-4, in-session changes in cortisol were evident, with significantly greater decreases in the AAI group (Cohen's d = -.40). This pattern was also observed at week-8, with an even stronger effect-size (d = -0.60). Concurrent symptoms of autism were associated with the in-session acute cortisol response. Specifically, higher parent-reported symptom scores were associated with steeper decreases in cortisol across the session at week 1 (r = -0.42, p < .01) and week-8 (r = -0.34 p = .05). At week-8 this association was stronger in the AAI group (r = -0.53) versus TAU (r = -0.25), with Cohen's q = 0.413) Discussion: AAI may influence HPA activity for children with ADHD. Concurrent symptoms of autism may be related to individual differences in the effect.